Hydration and properties of ternary cement with calcareous filler and slag - Irassar, E. F.; Bonavetti, V. L.; Menéndez, G.; Carrasco, M. F. (Revista ALCONPAT, 2015)
Limestone filler (F) produces an increase of early hydration due to the physical effect (filling andheterogeneous nucleation). The dilution effect reduces this benefit limiting the F content. Granulatedblast furnace slag reacts slowly causing the grain and pore size refinements, and improve mechanicaland durable properties. In this paper, the hydration of cements with F (0-20%) and GBFS (0-35%) isstudied using the model of Powers extended by Chen & Browers for slag. From the results of thehydration, the mechanical strength of concrete (w/cm = 0.50), and the pore segmentation process isanalyzed in relation to the sorptivity rate. Results show that filler content should be limited for anadequate mechanical strength and long term durable properties and slag content should be limited forappropriate early propertiesKeywords: calcareous filler; slag; resistance; capillary absorption; hydration.